Relasi Wahyu dalam Tiga Agama Samawi (Kajian terhadap Pemikiran Mohammed Arkoun) - Siti Nurmajah (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The revelation so far is reading by partially and exclusively way. Partial and exclusive here means only discussing only the religious groups. Each religion has its own truth claims. In this point, Arkoun’s idea about revelation found its signification. From his prespective which contemplate the revelation not only by Islamic view but also consider its relation to the two religion before Islam. This article aims to discuss the Arkoun’s idea about revelation and how the implication of his idea to the multi-religion discourse. The Abrahamic religion is Yahudi, Kristen, and Islam. Arkoun said that basically Yahudi, Kristen, and Islam are a social group which produce by the revelation. the dialogue between the divine religions can be opened and the exclusivity of reading the revelations can be eliminated through Arkoun's idea of revelation.